Integrating climate change adaptation into municipal masterplans through Strategic Environmental Assessment (SEA): A case study concerning Sardinia - Isola, Federica; Lai, Sabrina; Leone, Federica; Zoppi, Corrado (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Adaptation to climate change and the need to deal with its impacts pose in evidence how important it is to identify and implement new planning practices that integrate these profiles into land-use policy-making. Within this conceptual framework, the identification of a system of plan objectives and actions that characterize the integration of climate change adaptation into planning policies, with particular reference to the local scale, is of particular importance. In this study, a methodology for implementing this integration is proposed through the establishment of a logical framework for the construction of municipal masterplans through strategic environmental assessment, as a pathway in which plans are formed and developed, as part of the assessment process, through the identification of a strategic system of objectives and an operational system of planning actions based on the integration of climate change adaptation into the plan formation process.